Codes of ethics content: UK and Australian corporations. Issue 5 (2nd August 2019) - Wood, Greg; Whyatt, Georgina; Callaghan, Michael; Svensson, Goran
Abstract : Purpose: This study aims to compare the content of the codes of ethics of the top 50 corporations in the UK and Australia. Design/methodology/approach: The code of each of the 50 top companies listed on the London Stock Exchange and the 50 top companies listed on the Australian Stock Exchange based on market capitalization was read against an updated version of a previous code content classification system. Findings: This research provides valuable insights into the similarities and differences that exist between the expected ethical standards in corporations based in two historically linked and culturally related countries: corporate approaches that are worthy of comment. Research limitations/implications: This paper does provide a sound basis for further investigation and cross-country comparisons of corporate codes of ethics. Practical implications: The instrument used for classifying code content gives an insight into the top companies operating in the UK and Australia and what they consider important to cover within a code of ethics. Social implications: In light of increasing societal expectations of corporate ethical standards, this research study offers improved understanding of/insight into the development of codes of ethics as a means to guide organizational behaviours/conduct. Originality/value: This study proposes a contemporary instrument for the analysis of codes of ethics that has built upon the work of others over the past 30 years.